PARODIA I IRONIA JAKO STRATEGIE KOMUNIKACJI W PROGRAMIE SATYRYCZNYM „THE COLBERT REPORT” - Dunin-Wilczyński, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Many contemporary American satirical programs try to convey the importance of critical reception of media reality. Being one of such programs, The Colbert Report uses irony and parody to create comedic materials which blend commentary, serious information, and entertainment. The show’s host, Stephen Colbert, puts on a mask of a conservative news announcer commenting on current political and social affairs by constant parody, since Colbert never leaves his constructed persona, using exaggeration and absurdity to mock contemporary news media, politicians and ideologies. The aim of this paper is a phenomenological analysis of the strategies in which creators of The Colbert Report use parody and irony in media communication. The specific type of irony that Colbert uses is not sarcastic, but it is more of an ironic mode, a mechanism, which is supposed to emphasize the absurdity of a specific media situation. In The Colbert Report, one can differentiate three main ironic mechanisms: context denaturalization, demystification of rhetorical discourse, and intertextual allusions.